The role of mast cells in asthma - Bradding, Peter (Henry Stewart Talks, 2011)
Mast cell biology, Mast cell cytokines, Mast cell activation in asthma, Mast cell tissue microlocalisation in asthma, Mast cell-airway smooth muscle interactions as a key feature of asthma